Prenatal diagnosis of lissencephaly: A case report - Cerovac, Nataša; Terzić, Milan; Borković, Milan; Divac, Nevena; Stojanović, Radan; Prostran, Milica (Vojnosanitetski pregled, 2017)
Introduction. Lissencephaly (“smooth brain”) forms a major group of brain malformations due to abnormal neuronal migration. It can cause severe intellectual and motor disability and epilepsy in children. The prenatal diagnosis of this malformation is rare. Case report. We presented a case of the prenatal diagnosis of lissencephaly. A 30-year old pregnant woman was reffered to the hospital at the week 35 of gestation for magnetic resonance imaging (MRI) after an ultrasound examination demonstrated fetal cerebral ventriculomegaly. Fetal MRI of the brain showed “smooth”, agyrya cortex. The female infant was born at term with birth weight of 2,500 g and Apgar score 8, showing global developmental delay. Postnatal ultrasound and MRI confirmed classical lissencephaly. She is now 8 years old and has spastic quadriparesis, mental retardation and epilepsy. Conclusion. Confirmation of the ultrasound diagnosis with MRI is desirable for the prenatal diagnosis of lissencephaly.